NOVEL CHAKRA SADHANA YOGA-BASED TREATMENT APPROACH FOR POST-TRAUMATIC STRESS DISORDER (PTSD) AND DISSOCIATIVE IDENTITY DISORDER (DID)-A CASE STUDY (Proceedings of the Global Public Health Conference, 2023)
This study investigates the efficacy of yoga therapy in improving quality of life in a patient diagnosed with dissociative identity disorder with the application of ancient yogic chakra sadhana method. This case study is of 35year female who had six different dissociative characters of different age groups from 6years to 74years females. All these characters are identified as a distress caused due to sexual abuse. Intervention of the applied chakra sadhana was based on the 7 central chakras prepared along our spine from our sacrum at its base and up to that crown at the uppermost point of our head. It is referenced in old-fashioned Vedic writings. After the application of this therapy for the initial 15 days along with basic yoga asanas, pre and post clinical interview results are scaled as per APA’s PTSD checklist (PCL-5) and Diagnostic Statistical Manual (DSM-II). This clearly indicate the improvement of mental health in patient. Further follow up and medical check-ups are conducted weekly for post treatment of 2 months. Then the all six characters disappeared from her.
Keywords: Dissociative Identity Disorder; Chakra sadhana; Yoga therapy; Yoga; Post traumatic stress disorder (PTSD); Breathing Kriya and Pranayama